Methods of Modeling of Managers’ Competences in the Context of Sustainable Development - Olena KOTYKOVA; Oksana KOMAROVSKA; Oksana MATVIICHUK; Maryna RADCHENKO; Tetiana HOLINSKA (Communications of International Proceedings, 2020)
The factors influencing the formation and management of international teams of project managers in a multicultural environment are analyzed. The main problems in managing communications in international projects that are directly related to the human factor are identified and the existing approaches to solving such problems are analyzed. The set of key competences of project managers of international teams in a multicultural environment, which distinguish successful project managers, is defined. An approach to the development of project managers working in international teams in a multicultural environment has been developed taking into account the development of competences that determine a successful project manager.
Keywords: Sustainable development; competence; manager; team; communication management.